AB0197 INCREASED CIRCULATING ADIPONECTIN IS AN INDEPENDENT DISEASE ACTIVITY MARKER IN PATIENTS WITH RHEUMATOID ARTHRITIS: A CROSS-SECTIONAL STUDY USING THE KURAMA DATABASE. (2nd June 2020) - Katsushima, M.; Hashimoto, M.; Shirakashi, M.; Yoshida, T.; Yamamoto, W.; Murakami, K.; Murata, K.; Nishitani, K.; Tanaka, M.; Ito, H.; Matsuda, S.
Abstract : Background: Adiponectin is a major adipokine with pleiotropic effects on inflammatory conditions including rheumatoid arthritis (RA). Adiponectin generally has anti-atherogenic effects, and its serum level inversely correlates with body mass index (BMI) and visceral fat area (VFA). On the other hand, several studies have indicated a deleterious role of adiponectin in RA progression [1]. Recently, both low BMI and increased serum adiponectin have been reported as poor prognostic factors of RA [2, 3]. However, large-scale surveys have not been done focusing on both BMI and serum adiponectin, and it is unclear which factor provides further contribution to RA disease activity. In addition, the effects of biological disease-modifying antirheumatic drugs (bDMARDs) and Janus kinase (JAK) inhibitors on serum adiponectin are largely unknown. Objectives: To clarify the relationship among serum adiponectin, body composition, current disease activity and therapeutic agents of RA. Methods: We conducted a cross-sectional study in RA patients under treatment with agents including bDMARDs and JAK inhibitors. A total of 351 subjects from the Kyoto University RA Management Alliance cohort (KURAMA) were enrolled. We classified the participants into five body composition groups (overweight with or without visceral adiposity, normal with or without visceral adiposity, and underweight), according to the cut-off points for obesity and visceral fat used in Japan: BMI, 18.5 kg/m 2 for underweight and 25.0 kg/m 2 for obesity, and VFA, 100 cm 2 for visceral adiposity. Differences of continuous variables among the five groups were assessed by the Steel-Dwass test or one-way analysis of variance (ANOVA). We adopted a multiple standardized linear regression model to analyze effects of serum adiponectin level on DAS28-ESR. Results: Serum adiponectin levels (20.9±12.5 vs. 14.7±8.4 µg/ml, p < 0.001) and DAS28-ESR (3.04±1.0 vs. 2.63±0.9, p = 0.017) in the underweight group were significantly higher than those in the others. In multiple regression analysis, serum adiponectin level, but not BMI, was positively correlated with DAS28-ESR (estimate = 0.0127, p = 0.0258). Subanalysis also showed that the use of bDMARD or JAK inhibitor did not have an obvious influence on circulating adiponectin. Conclusion: In the multiple regression analysis we revealed a positive and independent correlation between serum adiponectin and DAS28-ESR in Japanese RA patients. Thus, serum adiponectin is an potential marker reflecting high disease activity of RA regardless of current medications. References: [1]Frommer KW, Zimmermann B, Meier FM, Schroder D, Heil M, Schaffler A, et al. Adiponectin-mediated changes in effector cells involved in the pathophysiology of rheumatoid arthritis. Arthritis Rheum. 2010;62(10):2886-99. [2]Kaufmann J, Kielstein V, Kilian S, Stein G, Hein G. Relation between body mass index and radiological progression in patients with rheumatoid arthritis. Journal of Rheumatology. 2003;30(11):2350-5. [3]Ebina K, Fukuhara A, Ando W, Hirao M, Koga T, Oshima K, et al. Serum adiponectin concentrations correlate with severity of rheumatoid arthritis evaluated by extent of joint destruction. Clin Rheumatol. 2009;28(4):445-51. Acknowledgments: We would like to thank to Ms. Sumie Nakagawa for management of blood specimens, Ms. Noriko Kitayama and Ms. Maki Yoneyama for support of the patients. We also thank Drs. Takao Fujii, Chicashi, Terao, Masahide Hamaguchi, Hiroyuki Yoshitomi, and Masahiro Ishikawa for their thoughtful comments. Disclosure of Interests: Masao Katsushima: None declared, Motomu Hashimoto Grant/research support from: Bristol-Myers Squibb, Eisai, and Eli Lilly and Company., Speakers bureau: Bristol-Myers Squibb and Mitsubishi Tanabe Pharma., Mirei Shirakashi: None declared, Tamami Yoshida: None declared, Wataru Yamamoto: None declared, Kosaku Murakami Speakers bureau: AbbVie, Eisai, and Mitsubishi Tanabe Pharma., Koichi Murata Grant/research support from: KMurata belong to a department that has been financially supported by four pharmaceutical companies (Mitsubishi-Tanabe, Chugai, AYUMI and UCB Japan)., Employee of: KMurata belong to a department that has been financially supported by four pharmaceutical companies (Mitsubishi-Tanabe, Chugai, AYUMI and UCB Japan)., Speakers bureau: KMurak has received speaking fees, and/or consulting fees from Eisai Co. Ltd, Chugai Pharmaceutical Co. Ltd., Pfizer Japan Inc, Bristol-Myers Squibb, Mitsubishi-Tanabe Pharma Corporation, UCB, Daiichi Sankyo Co. Ltd. and Astellas Pharma Inc., Kohei Nishitani Grant/research support from: KN belong to a department that has been financially supported by four pharmaceutical companies (Mitsubishi-Tanabe, Chugai, AYUMI and UCB Japan)., Masao Tanaka Grant/research support from: AbbVie, Asahi Kasei Pharma, Astellas Pharma, Ayumi Pharmaceutical, Chugai Pharmaceutical, Eisai, Mitsubishi Tanabe Pharma, Taisho Pharmaceutical, and UCB Japan. Speakers bureau: AbbVie, Asahi Kasei Pharma, Astellas Pharma, Bristol-Myers Squibb, Chugai Pharmaceutical, Eisai, Eli Lilly and Company, Janssen Pharmaceutical, Mitsubishi Tanabe Pharma, Novartis Pharma, Pfizer, Taisho Pharmaceutical, Takeda Pharmaceutical, and UCB Japan., Hiromu Ito: None declared, Shuichi Matsuda: None declared